Gastro-esophageal reflux disease among type-2 diabetes mellitus patients in a rural area (Medical Journal of Indonesia, 2015)
Background: One of the most neglected complications of diabetes mellitus (DM) is gastro-esophageal reflux disease (GERD) which arises from autonomic neuropathy and diabetic gastropathy related to the extent of DM. This study was done to find prevalence of GERD in DM patients with GERD-questionnaire (GERDQ), dietary factor proportion, and their association with other GERD risk factor in rural area. Methods: This cross sectional study was conducted in Puskesmas Pelaihari from August to September 2013. Subjects with DM aged ≥ 18 were selected consecutively from both newly and previously diagnosed patients with exclusion criteria: pregnancy, in proton-pump inhibitor therapy, and had other metabolic disease(s). DM was diagnosed with ADA criteria, while GERD was diagnosed in patients with score of ≥ 8 of Indonesian GERDQ. Results: There were 30 subjects (29.7%) with GERD among 101 patients with DM and dietary factors found in GERD patients were spicy diet (90%), high-fat food (90%), irritative beverages (87%), and irritative diet (23%). Only female gender was associated with GERD vs non-GERD in DM patients (87% vs 68%, p = 0.048). Meanwhile, duration of DM (2 [0-13] vs 2 [0-19], p = 0.976), obesity (37% vs 38%, p = 0.897), age (53.2±10.5 vs 54.7 ± 9.3, p = 0.481), and uncontrolled diabetes (90% vs 94%, p = 0.421) were not associated with the GERD among DM patients. Conclusion: Prevalence of GERD in DM is somewhat high in this study. Female group with DM needs to be screened for GERD as early as possible.